Fatal Waterhouse-Friderichsen syndrome due to Neisseria meningitidis group B in a paediatric patient during the phone consultation era - Marta Serafin; Ewa Czerwińska; Marian Koźbiał; Mariusz Leszczyński; Leszek Szenborn (Termedia Publishing House, 2023)
Owing to uncharacteristic initial symptoms and rapid progression, invasive meningococcal disease is still a challenge to diagnose and treat, even in high-income countries. Waterhouse-Friderichsen syndrome is a potentially fatal complication of invasive meningococcal disease, presenting as acute adrenal insufficiency due to haemorrhagic necrosis of the adrenal glands. We report a case of 5.5-year-old boy who presented to the hospital with fever, impaired consciousness, vomiting, and upper respiratory tract infection symptoms. Despite prompt diagnosis of invasive disease and adequate treatment, the patient died. We underline the need to increase parents' knowledge and better access to vaccines against meningococci for Polish paediatric patients. Paediatricians and primary care physicians must remain alert and be ready to suspect invasive meningococcal disease in their patients.